Path Analysis Effect Corruption, Tax, Inequality Economy and Poverty Level Against Percentage of Teenagers Not Attending School - Puspitasari, April; Khinara, Ejia; Rodiyah , Khusni Sinta; Sunardi, Shintia Putri; Daoud, Jamal I (Integra: Journal of Integrated Mathematics and Computer Science, 2025)
This research uses path analysis to examine the relationship between variables: Adolescents who are not in school (NS), corruption (CR), taxes (TR), economic inequality (EN), and poverty (EP). The aim of this research is to determine whether there is a direct effect of CR on TR, a direct effect of TR on EN, a direct effect of TR and EN on EP, and a direct effect of ENand EP onNS. The analysis results show that there is no direct effect of CR on TR but it is still meaningfulness with a value of 0.2588. The direct effect of CR on TR is-0.6984. There is a direct effect of TR and EN on EP. The effect of TR on EP is 0.1681. The effect of EN on EP is-0.5735. There is a direct effect of EN and EP on NS. The effect of EN on NS is 0.3859. The effect of EP on NS is 0.6037.